Moral externalization may precede, not follow, subjective preferences. (17th May 2018) - Kaznatcheev, Artem; Shultz, Thomas R.
Abstract: We offer four counterarguments against Stanford's dismissal of moral externalization as an ancestral condition, based on requirements for ancestral states, mismatch between theoretical and empirical games, passively correlated interactions, and social interfaces that prevent agents' knowing game payoffs. The fact that children's externalized phenomenology precedes their discovery of subjectivized phenomenology also suggests that externalized phenomenology is an ancestral condition.